PENGARUH ZPT GA₃ DAN ZPT ALAMI KATANG-KATANG TERHADAP PERTUMBUHAN BIBIT TANAMAN MATOA (Pometia pinnata) - Hasraf Haitullah; Fiana Podesta; Dwi Fitriani; Ririn Harini (University of Prof. Dr. Hazairin, SH, 2025)
This study aims to evaluate the effect of the administration of Growth Regulating Substances (ZPT) gibberelin (GA₃) and natural ZPT derived fr om katang-katang plants on the growth of matoa seedlings (Pometia pinnata). The study was conducted using a factorial Completely Randomized Design (RAL) with two factors, namely GA₃ concentration (A0 = no treatment, A1 = 50 ppm, A2 = 65 ppm, and A3 = 80 ppm) and natural ZPT concentration of katang-katang (K1 = 15 ppm, K2 = 30 ppm, and K3 = 45 ppm). The observed parameters included plant height, number of leaves, leaf width at the age of 14, 28, 42, 56, 70, and 84 days after planting (HST), as well as the length and number of roots at the age of 84 HST. The results showed that GA₃ administration had a significant effect on plant height, leaf count, root length, and root count, with a concentration of 65 ppm (A2) showing the best results in most vegetative growth indicators. Meanwhile, the natural ZPT treatment of katang-katang also had a significant effect on the number of leaves and roots, where the concentration of 30 ppm (K2) resulted in the highest number of roots. The interaction between the two types of ZPT had a significant effect on the root count parameters, with the combination of GA₃ 65 ppm and 30 ppm katang-kaang providing the most optimal results. Overall, the combination of synthetic ZPT GA₃ and natural ZPT is effective in increasing the vegetative growth of matoa seedlings and has the potential to be an environmentally friendly alternative in plant propagation.